KEJADIAN KATARAK PADA BAKSOS LPM UNIVERSITAS YARSI DAN PERDAMI DKI JAYA DI RUMAH SAKIT DEPOK - Saskia Nassa Mokoginta; Atiek Indriawati; Tri Agus Haryono; Himmi Marsiati (Info Abdi Cendekia, 2020)
Results of the 2014-2016 Rapid Assessment of Avoidable Blindness (RAAB) Blindness Survey by the Association of Indonesian Ophthalmologists (PERDAMI) and the Ministry of Health Research and Development Agency in fifteen provinces (West Sumatra, North Sumatra, South Sumatra, DKI Jakarta, West Java, Java Central, East Java, South Kalimantan, Bali, NTB, NTT, North Sulawesi, South Sulawesi, Maluku and West Papua), it is known that the blindness rate reaches 3% and cataracts are the highest cause of blindness (81%). The survey was conducted with the target population aged 50 years and over. Life expectancy (UHH) in Indonesia continues to increase significantly. The average UHH increased from the age of 63 in 1990 to 69 in 2017, meaning that an increase in life expectancy will have an impact on increasing degenerative diseases. Cataract is a degenerative process that is strongly influenced by age, therefore this case will continue to increase in line with the increasing number of elderly people. Although cataracts can also occur in infants and children, which are caused by intrauterine processes such as infection and malnutrition during childhood, these cases are very rare. YARSI SAVE VISION, YARSI University Sevice Community has played a role in reducing the blindness rate by carrying out cataract surgery services. On March 24, 2018, cataract surgery was carried out on 50 patients at the Depok General Hospital, held in collaboration with PERDAMI JAYA and the Depok Regional General Hospital, with Operation Technique, ICCE (Intracapsular Cataract Extractio), SICS (Small Incision Cataract Surgery)/ ECCE (Extra Capsular Cataract Extraction) and Phacoemulsification